Information and software technologies : 21st International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015, Proceedings /: 21st International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015, Proceedings. (2015) - Unknown
No abstract available